2016
DOI: 10.7150/jca.14582
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma and Diffusion-Weighted MRI: Detection and Evaluation of Treatment Response

Abstract: Differentiating between cancerous tissue and healthy liver parenchyma could represent a challenge with the only conventional Magnetic Resonance (MR) imaging. Diffusion weighted imaging (DWI) exploits different tissue characteristics to conventional Magnetic Resonance Imaging (MRI) sequences that enhance hepatocellular carcinoma (HCC) detection, characterization, and post-treatment evaluation. Detection of HCC is improved by DWI, infact this technology increases conspicuity of lesions that might otherwise not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 51 publications
(61 reference statements)
0
27
0
Order By: Relevance
“…Studies investigating the utility of DWI have demonstrated promising results for assessing prognosis, predicting response, distinguishing tumor from treatment effect, and monitoring response to therapy in patients with HCC. 18 , 19 , 20 , 21 , 22 ,…”
Section: Mri Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies investigating the utility of DWI have demonstrated promising results for assessing prognosis, predicting response, distinguishing tumor from treatment effect, and monitoring response to therapy in patients with HCC. 18 , 19 , 20 , 21 , 22 ,…”
Section: Mri Protocolmentioning
confidence: 99%
“…Regenerative nodules may present accumulation of iron which results in low signal intensity on T1-and T2-weighted imaging. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ,…”
Section: Imaging Features On Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…The diffusion restriction, which can be quantified into an apparent diffusion coefficient (ADC), is therefore a way of non-invasively measuring the cellularity of (tumor) tissue. Prior studies have found an inverse correlation between ADC value and histological tumor grade and microvascular invasion [8][9][10][11]. Kamel et al first demonstrated the feasibility of DWI for response assessment after TACE by showing that an increased tumoral ADC at 4-6 weeks after TACE corresponded to radiological and histological response [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, OATP8 expression level reduces prior to complete neoangiogenesis[ 12 ] and the use of hepatospecific contrast media in MRI is considered a “new” HCC diagnostic tools that allows either to increase sensitivities for detection of HCC of all sizes[ 13 ] or would make it possible to identify preneoplastic lesions, such as HGDNs[ 14 ]. Furthermore, MRI offers additional imaging sequences that can be helpful in nodule characterization, including T2-weighted imaging (T2-WI) and diffusion-weighted imaging (DWI), which provides information on cellularity and has shown additional value to gadolinium-enhanced MRI by increasing the detection rate of HCC[ 15 ]. However, precise differentiation of preneoplastic lesions remain uncertain to date.…”
Section: Introductionmentioning
confidence: 99%